Black-Pigmented Marine Pseudomonas aeruginosa Exhibiting Anti-Bacterial Activity against Multidrug-Resistant (MDR) Wound Infection Bacteria - Prastiyanto, Muhammad Evy; Darmawati, Sri; Daryono, Budi Setiadi; Retnaningrum, Endah (HAYATI Journal of Biosciences, 2024)
The urgency of multidrug-resistant (MDR) bacterial infections in wounds is a significant concern due to the high prevalence of MDR in healthcare settings. Black pigmented marine bacteria, strain PS1C, were isolated from marine sediment on Awur Beach Jepara, Central Java, Indonesia, and cultured in the laboratory. The aim of this research includes molecular identification of strain PS1C, extracting black pigment from strain PS1C, isolation of MDR bacteria from wounds, and evaluating the antibacterial activity of black pigment from strain PS1C against MDR bacteria isolates of wound infections. We examined the 16S rRNA gene sequences strain PS1C to identify the species. Then, the black pigment from PS1C was extracted using methanol: acetone (7:3) solvent. Antibacterial activity was evaluated against MDR bacteria from wounds with the microdilution method. A black-pigmented bacterium was isolated and identified as Pseudomonas aeruginosa PS1C. We found that the black pigment from P. aeruginosa PS1C can be developed as an antibacterial agent against the MDR bacterial isolate of wounds with MIC and MBC values of 6.25-12.5 mg/ml and 6.25-25 mg/ml, respectively. In conclusion, the study's findings highlight the potential of the extract of black pigment from P. aeruginosa PS1C as an antibacterial agent against wound-causing MDR bacteria and reinforce previous research into P. aeruginosa can be isolated from marine sources. Additional in vivo investigations and the identification of the antibacterial activity's mode of action are required.